A construção da hegemomia empresarial : o caso do Movimento Repensando Maringá (1994-2004) - Gini, Sérgio (2007)
In this research we approach the process of construction of the hegemony of the enterprises in Maringá, Paraná, from the second half of the decade of 1990 until the year of 2004, year of the election of the current mayor of the city. This process was given for intermediary of the Movimento Repensando Maringá that articulated and congregated the different segments of enterprise groups - employers, commerce, industry and rendering of services - to change itself into a leading force capable to dictate some politics routes of the city from the idea-force of the economic development. The Movimento Repensando Maringá gave origin to the Conselho de Desenvolvimento Econômico de Maringá - Codem, created for municipallaw in 1997 and responsible for the management of the Fundo Municipal de Desenvolvimento Econômico, beyond formulating the politics of development of the city. Formed for diverse groups of segments and different entities - more than 80 -, Repensando Maringá was controlled since its beginning for the Associação Comercial e Empresarial de Maringá - ACIM, whose politics strategies allowed it to impose itself as legitimate leadership on ali the set. Although it was presented as a neutral movement and without politics matrixes the proposals of Repensando had served of base for the plans of govemment of the elected mayors in 1996, 2000 (with the almost declared support to the candidate of the PT, in as the second turn) and in 2004 when the elected candidate was a member of the Codem and council member of the Associação Comercial. The hegemonic project managed by the leading enterprise group registered the city administrations in this period. In this direction, we believe that this research offers subsidies to think about the action ways politics of the enterprises and to understand the motivations that had taken it if to move away from the partisan politics and to act in the direct influence of the Executive.